Analisis Semiotika Video Edukasi Darurat Eksploitasi Anak - Purwanto, Farelino Arsyi Vernanda; Widyasari; Wibisono , Aryo Bayu (STAIN Bengkalis, 2025)
Exploitation of children under the age of 13 in Indonesia is a serious social problem, covering economic, sexual and social exploitation. This research aims to design an educational video titled